Gambaran Pembentukan Identitas Agama pada Religious Disbeliever Usia Emerging Adult - Rizikita Imanina; M. Akhyar (Jurnal Ilmiah Psikologi MIND SET, 2018)
Emerging adulthood is a phase of life stages that provide opportunities in exploring identity before entering adulthood phase. One of thing explored in this transition phase is religious belief. As the doubt increases of the emerging adults towards religious belief that they learned from their parents, it has led them to religious disbeliever. The aim of this research is to see the process of exploration in identity to become a religious disbeliever. Basic descriptive qualitative study method is used to approach the objectives of this research by using interview and observation methods in collecting data. Subject of interview are consisting of two religious disbeliever who were a muslim. The result of this research showed the process of identity forming by the subject not only seen by neither exploration process nor commitment achievement, but also by external figure such as parent and social circle of friends.